The effect of fluorination on the photovoltaic performance of the D–A copolymers containing naphtho[2, 3-c]thiophene-4, 9-dione and bithiophene moieties. Issue 31 (20th July 2016) - He, Dan; Geng, Xinjian; Ding, Liming
Abstract : Fluorine improves the planarity of the polymer backbone via its lock-up function. Polymer PFNTDFBT shows a high mobility and its solar cells gave a PCE of 7.79%. Abstract : Four D–A copolymers, PNTDBT, PFNTDBT, PNTDFBT and PFNTDFBT, were prepared for systematically studying the effect of fluorination on photovoltaic performance. The fluorinated copolymers, PFNTDBT, PNTDFBT and PFNTDFBT, gave higher FF (∼70%) than PNTDBT due to their reduced bimolecular recombination and balanced mobilities. PNTDFBT with F on the BT unit shows a higher mobility than that of PFNTDBT with F on the NTD unit, leading to a higher J sc . PFNTDFBT gave the highest PCE, 7.79%, which might result from its higher mobility and the optimal miscibility between PFNTDFBT and PC71 BM.